The 5-Repetition Sit-to-Stand Test as an Outcome Measure for Pulmonary Rehabilitation in Subjects With Asthma - Zampogna, Elisabetta; Pignatti, Patrizia; Ambrosino, Nicolino; Cherubino, Francesca; Maria Fadda, Anna; Zappa, Martina; Spanevello, Antonio; Visca, Dina (Respiratory care, 2021)
The 5-repetition sit-to-stand test (5STS) is valid and responsive in subjects with COPD, but there is a lack of information in subjects with asthma. We aimed to evaluate the usefulness of the 5STS as an outcome measure of pulmonary rehabilitation in subjects with asthma as compared to subjects with COPD. We conducted a retrospective evaluation of subjects with asthma or COPD who underwent pulmonary rehabilitation. Both before and after in-patient pulmonary rehabilitation, subjects underwent the 5STS and the 6-min walk test; dyspnea was assessed with the Medical Research Council scale and the Barthel Index for dyspnea, and the burden of symptoms was assessed with the COPD Assessment Test. Of 475 patients admitted during the study period, 103 subjects with asthma and 108 with COPD were included. After pulmonary rehabilitation, the 5STS improved significantly in both populations (by a median value of -1.7 s [interquartile range -4.2 to -0.5] and -1.1 s [interquartile range -3.4 to 0.0] in subjects with asthma and COPD, respectively; < .001 for both, = .17 between groups) independent of body mass index, as did other outcome measures. The baseline 5STS correlated slightly but significantly with age, the 6-min walk test, and the Barthel Index for dyspnea in both populations, whereas it correlated significantly with the Medical Research Council scale only in subjects with asthma and correlated with COPD Assessment Test only in subjects with COPD. No significant correlations between changes in the 5STS and in other assessed outcome measures before and after pulmonary rehabilitation were observed in subjects with asthma, whereas changes in the 5STS correlated slightly but significantly only with changes in 6-min walk test in subjects with COPD. The 5STS was a reliable outcome measure of pulmonary rehabilitation in subjects with asthma. It must be specifically assessed and may be included in the tools for assessment of effects of pulmonary rehabilitation also in these patients.